2020
DOI: 10.7717/peerj.9544
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of non-lethal predator deterrents to reduce livestock losses to leopard attacks within a multiple-use landscape of the Himalayan region

Abstract: Lethal measures are widely adopted by local communities and governments to manage human-wildlife conflicts. Such measures lead to large scale decline of carnivore populations globally with trophic cascades on ecosystems and questionable impacts on human-wildlife conflicts. Mitigating human-carnivore conflicts through non-lethal measures will protect endangered predators and secure livelihoods. However, information on the effectiveness of such measures are extremely limited and hence cannot be applied in develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…The relationship between detections and predation is complex. In another study of Foxlight effectiveness, Naha et al (2020) found that Foxlights led to a significant decline in livestock predation but no difference in leopard visitation between experimental and control sites. Thus, deterrents may diminish a carnivore's willingness to expend the energy and assume the risk associated with predation without altering visitation rates (Wilkinson et al, 2020).…”
Section: Ecological Effectivenessmentioning
confidence: 95%
See 1 more Smart Citation
“…The relationship between detections and predation is complex. In another study of Foxlight effectiveness, Naha et al (2020) found that Foxlights led to a significant decline in livestock predation but no difference in leopard visitation between experimental and control sites. Thus, deterrents may diminish a carnivore's willingness to expend the energy and assume the risk associated with predation without altering visitation rates (Wilkinson et al, 2020).…”
Section: Ecological Effectivenessmentioning
confidence: 95%
“…Foxlights are predation deterrents that flash randomly timed and colored lights in all directions from sundown to sunup to mimic lights that are associated with human presence, and are designed to be used based on line-of-sight. We chose Foxlights because of their reported ecological effectiveness (Ohrens et al, 2019a;Naha et al, 2020) and growing popularity. We evaluated the effects of Foxlights on coyote (Canis latrans) activity in a sheep production operation in Northern California, as coyotes pose the most significant predation risk in this geographical context (USDA, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal and opportunistic surveys were carried out in the study area from 2015 to 2020 in randomly selected villages adjacent to the forests, natural habitats of black bear and having a confirmed damage reports or sightings of black bear in that area (Karanth et al, 2012;Perveen and Muhammad, 2013;Wahid et al, 2017). Key personals including hunters, staff of the Wildlife department and elder farmers were targeted in each survey to avoid bogus and exaggerated information (Naha et al, 2020;Perveen and Muhammad, 2013;Wahid et al, 2017). Questionnaires were administered face to face to randomly selected households in communities associated with the protected (National Parks and Game Reserves) as well as non-protected areas Karanth et al, 2012;Mir et al, 2015).…”
Section: Questionnaire Surveymentioning
confidence: 99%
“…Deterrence, based on their operation, are classified as active, passive, vigilant, lethal, non-lethal, sensory, repellent etc. and have a species-specific use (Anthony et al, 2010;Hill, 2016;Naha et al, 2020;Scotson et al, 2014;Ueda et al, 2018). Though electric wire fencing, traps and repellents deter a wide range of attacking animals (Anthony et al, 2010), none of them are used in the study area.…”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…One of many techniques is the use of flashing lights as a visual repellent that may mimic human activity to deter wildlife. This technique has largely been proven effective in protecting livestock from depredation by carnivores at night (Lesilau et al 2018, Ohrens et al 2019, Okemwa et al 2018, Naha et al 2020, Sutherland et al 2021, Wanjira et al 2021). Yet without reinforcement with aversive human activity, such as lethal control, the efficacy of flashing lights as a visual deterrent may be limited (Hall & Flemming 2021).…”
Section: Introductionmentioning
confidence: 99%